COMPARATIVE STUDY OF EPIDURAL 0.5% LEVOBUPIVACAINE AND EPIDURAL 0.5% LEVOBUPIVACAINE WITH DEXMEDETOMIDINE ON SENSORY BLOCKADE FOR PATIENTS UNDERGOING ELECTIVE INFRAUMBILICAL AND LOWER LIMB SURGERIES - DR.ARUN POTHAN RAJ.V; DR.NIRANJAN KUMAR (International Journal of Pharma and Bio Sciences, 2015)
Levobupivacaine , the pure S enantiomer of bupivacaine has emerged as a safe local anaesthetic than its racemic counterpart. Dexmedetomidine the novel selective alpha2 adrenergic agonist has several advantages when given through epidural route as an adjuvant. To compare plain 0.5% Levobupivacaine with Dexmedetomidine and 0.5% levobupivacaine epidurally for the time of onset of sensory blockade and its duration. 60 patients undergoing infraumblical and lower limb surgeries were randomized to two groups. Group A(n=30) received only Levobupivacaine 0.5% 20 ml epidurally. Group B(n=30) received 50 mcg of dexmedetomedine with Levobupivacaine 0.5% 20 ml epidurally. The time of onset of sensory blockade, maximum height of sensory blockade and duration of blockade were noted. Statistical work done by student t test and chi-square test and p<0.05% were taken to be significant. Dexmedetomidine fastens the onset of sensory blockade and the duration of blockade without any significant adverse effects. : We conclude that Dexmedetomidine can be used as an adjuvant to Levobupivacaine which fastens the onset and prolong the duration of sensory blockade.